Implementation of School Rules in Forming Students' Disciplined Character - Nur Hidayah; Sukari Sukari (Abjadia : International Journal of Education, 2026)
This study aims to describe the implementation of school rules and regulations in developing students' disciplinary character at MTs Sholihiyyah Kalitengah, Mranggen, Demak, and to analyse the impact of these implementations. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and validated through source and technique triangulation. The findings indicate that school rules and regulations are consistently implemented through daily habituation activities such as morning assembly, religious practices, literacy programmers, and cleaning duties. Teachers’ exemplary behavior, structured supervision, and the application of educational sanctions play a significant role in internalising disciplinary values among students. The implementation of these rules positively affects students’ time discipline, neatness, manners, and academic as well as social responsibility. However, this study is limited to a single Islamic junior high school, and therefore the findings are not intended to be generalised to other educational contexts. Nevertheless, the results suggest that the continuous enforcement of school rules, supported by teachers’ role modelling and school-wide commitment, can serve as a practical framework for strengthening students’ disciplinary character in similar educational settings.